Emergence of conflict for oil incomes: a historic preamble to present economic trend (1917 to 1936) (2007)
The emergence of conflict for oil incomes appropriation by the Venezuelan state as the national soil owner dates to the historical period of 1917 to 1936. The solution of such conflict favored the tenants, foreign oil companies, since strength correlation benefited them. These facts generated lack of trust towards foreign investment, today evidenced in the cautious way in which the Oil Association faces the national debate between official enterprises and transnational companies.